2015
DOI: 10.4028/www.scientific.net/amm.754-755.406
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alkaline Activator Ratio to Mechanical Properties of Geopolymer Concrete with Trass as Filler

Abstract: This paper describes the effect of alkaline activator ratio (Na2SiO3/NaOH) to mechanical properties of geopolymer concrete. The mechanical properties of geopolymer concrete were assessed by setting time, split tensile strength and porosity. Fly ash was used as a cement substitute, and trass used as filler. While, Natrium hydroxide (NaOH) and Sodium Silicate (Na2SiO3) was applied as alkaline activator. In this study, NaOH concentration eight and ten molar with an alkaline activator ratio Na2SiO3/ NaOH by mass: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 8 publications
2
17
1
1
Order By: Relevance
“…So it can be concluded that the number of open pore is inversely proportional to the compressive strength and density of geopolymer paste. This is consistent with previous studies which stated that increasing the number of open pore will decrease the compressive strength and density of geopolymer paste [14]. Fernadez was also stated that particle size and particle distance play an important role in developing properties of geopolymer binder.…”
Section: Porositysupporting
confidence: 81%
See 1 more Smart Citation
“…So it can be concluded that the number of open pore is inversely proportional to the compressive strength and density of geopolymer paste. This is consistent with previous studies which stated that increasing the number of open pore will decrease the compressive strength and density of geopolymer paste [14]. Fernadez was also stated that particle size and particle distance play an important role in developing properties of geopolymer binder.…”
Section: Porositysupporting
confidence: 81%
“…Open pore is a pore that is permeable so that it can be penetrated by water and air, while the close pore is impermeable so that water and air cannot pass [14].…”
Section: Porositymentioning
confidence: 99%
“…In geopolymer concrete, this fly ash will replace the cement as binder. However, compared to the cement concrete, geopolymer concrete has lower workability [5] due to the sort setting time of geopolymer concrete. Geopolymer concrete prone to harden before delivered to the construction site located far away from the batching plant.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are different results when usingmolarity of 10MNaOH, where the compressive strength increase is based on the increase of Na 2 SiO 3 to NaOHratios. The highest compressive strength can be achieved in ratio of 2.5 by 30.97 MPa [11]. This means that the geopolymer compressive strength can be increased by modifying the mixture namely by changing Na 2 SiO 3 to NaOH ratio as well as the molarity of NaOH.…”
Section: A Resultsmentioning
confidence: 78%
“…This means that the geopolymer compressive strength can be increased by modifying the mixture namely by changing Na 2 SiO 3 to NaOH ratio as well as the molarity of NaOH. So that, natural aggregate compressive strength of 33.0 MPa [11] can be achieved by fly ash geopolymer paste. Even fly ash geopolymer pastes is greatly possibly to have higher compressive strength.The activator ratio and the concentration of NaOH solution have an important role to the compressive strength value of the geopolymer paste.…”
Section: A Resultsmentioning
confidence: 99%